Effect of Anti-Corruption Law adoption on firm value of Brazilian companies listed on Ibovespa - Ramos, Fernando Maciel; Hohn, Gabrielle Secchi; Vargas, Lucas Antônio (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
Currently, corruption is a highly addressed issue. As anti-corruption practices, which are increasingly required in the financial market, this study aims to analyze the effect of adopting the Anti-Corruption Law on Brazilian companies’ firm value listed on Ibovespa. The sample consisted of 229 observations from 2014 - 2018. Based on the econometric estimates, the results demonstrated a positive effect of adopting anti-corruption practices on companies’ firm value. Given the problem of corruption in the Brazilian market, this study contributes to information that encourages the regulation of the market, organizations, and stakeholders in adopting and disclosing anti-corruption practices.